Effect of “Sape" Music Therapy on Decreasing Anxiety, Physiological Response, and Sleep Quality among Post Sectio Caesarea Patients - Ta'di; Andarias Pilang; Dyah, Dina Indrati; Pujiastuti, Rr. Sri Endang (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Sectio Caesarea is an act of delivery assistance through a surgical procedure that can cause disturbances such as changes in anxiety, physiological responses, and sleep quality. Objective: This study aims to analyze the effectiveness of "sape" music therapy on changes in anxiety, physiological responses, and sleep quality in post-operation Sectio Caesarea patients. Methods: True experiment with pre-test and post-test randomized control group design. The intervention group (n=21) received “sape” music therapy and routine nursing care in the midwifery room, while the control group (n=21) only received routine nursing care. Results: After giving "sape" music therapy, it was found that there was a difference in the decrease in anxiety on the average score of the Hamilton Anxiety Rating Scale (p = 0.000), there was no difference in the reduction of systolic blood pressure (? = 0.984) and diastolic blood pressure (p = 0.905), there is a difference in the decrease in pulse rate (p = 0.004), there is a difference in the reduction in respiratory rate (p = 0.035), and there is a difference in the increase in sleep quality (? = 0.005). Conclusion: "Sape" music therapy is effective in reducing anxiety, pulse, and respiratory rate, stabilizing systolic and diastolic blood pressure within normal limits, and improving sleep quality in post-operation Sectio Caesarea patients. Recommendation: Further studies can be carried out to determine whether extending the time of the “sape" music therapy intervention will have the desired impact, namely, reducing the systolic and diastolic blood pressure more optimally